PENGARUH CUSTOMER RELATIONSHIP MANAGEMENT (CRM) DAN KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN PADA BUSINESS GOVERNMENT AND ENTERPRISE SERVICE (BGES) PT. TELKOM WITEL SULTRA - Anna Stasia Octavia; Patwayati Patwayati; Nursaban Rommy (Pascasarjana Universitas Halu Oleo, 2019)
This research is aimed to determine and analyze the Effect of Customer Relationship Management (CRM) and Service Quality on Customer Loyalty through Customer Satisfaction in Business Government and Enterprise Service (BGES) of PT. Telkom Witel in Southeast Sulawesi, by applying SEM analysis. One of the benefits expected is that this research can be implemented as a data resource by PT. Telkom Witel of Southeast Sulawesi. Based on the results obtained from research and discussion, it can be concluded as follows: Customer relationship management (CRM) has a positive and significant effect on customer satisfaction at PT Telkom Witel of Southeast Sulawesi; Service quality has a positive and significant effect on customer satisfactionat PT Telkom Witel of Southeast Sulawesi; Customer relationship management (CRM) has a positive and significant effect on customer loyalty at PT Telkom Witel of Southeast Sulawesi; Service quality has a positive and significant effect on customer loyalty at PT Telkom Witel of Southeast Sulawesi; Customer satisfaction has a positive and significant effect on customer loyalty at PT Telkom Witel of Southeast Sulawesi;Customer relationship management (CRM) has a positive and significant effect on customer loyalty through customer satisfaction at PT Telkom Witel of Southeast Sulawesi; Service quality has a positive and significant effect on customer loyalty through customer satisfaction at PT Telkom Witel of Southeast Sulawesi.Keywords: CRM, Service Quality, Customer Satisfaction and Customer Loyalty